DOMINASI AYAH ATAU IBU? ANALISIS PERANAN ORANG TUA DALAM PENDIDIKAN ANAK DI LINGKUNGAN KELUARGA - Yuni Setia Ningsih (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Chance and job opportunities to work can be gained by anyone, without limiting men as fathers or women as mothers. This equality has implications for the dominance of children education in the family environment. This paper aims to analyze how the dominance and ways of fathers or mothers as parents in educating their children. The data of this study were sourced from a group of students who were respondents. The results showed that mothers have a dominant role in educating children. However, both of them pay attention to the bringing up of their character of discipline, responsibility and independen. The different side lies in the way the father and mother in shaping the character of the child. Therefore, the results of this study are important to be exposed as an effort to balance the information that fathers and mothers with various activities and professions still have an interest in children education.